O embeddedness relacional e sua influência no surgimento de inovações em subsidiárias estrangeiras instaladas no Brasil - Isaac, Victor Ragazzi (2019)
This thesis aims to analyze the factors that influence the development and transformation of local innovations into global innovations of emerging market subsidiaries. We believe that the relational embeddedness of subsidiaries with the external local network is paramount for the development of local innovations. On the other hand, the transformation of local innovations into global ones is due to the level of innovation developed by the subsidiary located in an emerging market. We also believe that the transformation of local innovations into global innovations will occur when subsidiaries have previously transferred reverse knowledge in functional areas. Reverse knowledge transfers therefore indicate an internal embeddedness, essential for local innovation to be transformed into global innovation. Our sample consisted of 131 foreign subsidiaries operating in Brazil. Using the Structural Equation Modeling technique, the results corroborate our hypotheses and show that the relational embeddedness of subsidiaries to the external LAN is positively associated with local innovation, which is transformed into global innovation, especially when innovation is developed in the functional areas of the network. subsidiary with previous transfers of reverse knowledge. With this, we have developed implications for the field of subsidiary management research, specifically to understand the role of local innovation of foreign subsidiaries in emerging markets.